2016
DOI: 10.1186/s12944-016-0350-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of statins in patients with diabetic nephropathy: a meta-analysis of randomized controlled trials

Abstract: BackgroundThe effects of statins in patients with diabetic nephropathy are controversial. With increasing interest in the potential therapeutic role of statins in diabetic nephropathy, it is essential to evaluate its real effects.MethodsPubMed, EMBASE, Web of Science databases, Cochrane Central Register of Controlled Trials and China National Knowledge Infrastructure were systematically searched for randomized controlled trials (RCTs) of statins in patients with diabetic nephropathy.ResultsFourteen trials with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 33 publications
0
35
0
3
Order By: Relevance
“…[208][209][210] These drugs also have had favourable effects on renal function in clinical trials, particularly in patients with diabetes; long-term therapy reduces albuminuria and retards the decline in glomerular filtration rate. 9,211,212 Similar benefits to the kidney have been noted in experimental diabetes; in these studies, statins prevent oxidative stress and cellular injury as well as the inflammatory, proliferative and fibrotic changes that are characteristic of diabetic chronic renal disease. [213][214][215][216][217][218][219][220] These favourable effects cannot be fully explained by the actions of these drugs on lipids; other lipid-lowering drugs exert little or modest effects on albuminuria and may worsen renal function in patients with diabetes.…”
Section: Inhibitors Of Aldosterone Action and Cholesterol Synthesismentioning
confidence: 65%
See 2 more Smart Citations
“…[208][209][210] These drugs also have had favourable effects on renal function in clinical trials, particularly in patients with diabetes; long-term therapy reduces albuminuria and retards the decline in glomerular filtration rate. 9,211,212 Similar benefits to the kidney have been noted in experimental diabetes; in these studies, statins prevent oxidative stress and cellular injury as well as the inflammatory, proliferative and fibrotic changes that are characteristic of diabetic chronic renal disease. [213][214][215][216][217][218][219][220] These favourable effects cannot be fully explained by the actions of these drugs on lipids; other lipid-lowering drugs exert little or modest effects on albuminuria and may worsen renal function in patients with diabetes.…”
Section: Inhibitors Of Aldosterone Action and Cholesterol Synthesismentioning
confidence: 65%
“…Inhibitors of HMG CoA reductase (eg, pravastatin, atorvastatin and rosuvastatin) are routinely prescribed to patients with diabetes or glucose intolerance, because they reduce the risk of major atherosclerotic ischemic events . These drugs also have had favourable effects on renal function in clinical trials, particularly in patients with diabetes; long‐term therapy reduces albuminuria and retards the decline in glomerular filtration rate . Similar benefits to the kidney have been noted in experimental diabetes; in these studies, statins prevent oxidative stress and cellular injury as well as the inflammatory, proliferative and fibrotic changes that are characteristic of diabetic chronic renal disease .…”
Section: Effect Of Drugs Used In Diabetes On the Sodium‐hydrogen Exchmentioning
confidence: 96%
See 1 more Smart Citation
“…Chronic kidney disease (CKD) has been associated with NAFLD/NASH, especially in T2DM patients, thus further increasing individual's CV risk [13][14][15] . Statins and some antidiabetic drugs, including some sodium glucose cotransporter 2 inhibitors and glucagon-like peptide 1 receptor agonists, have been shown to improve albuminuria and renal dysfunction, as well as prevent/delay CKD progression [16][17][18][19][20][21][22] . Oshakbayev et al 1 do not provide any data on kidney function despite commenting on changes in urine composition.…”
Section: Dear Editormentioning
confidence: 99%
“…Apart from LDL-C risk reduction, statins may exert further benefits in DM patients [3]. In this context, it has been shown that statins can improve urinary albumin excretion rates and albuminuria, especially in type 2 DM patients with diabetic nephropathy [4]. Statins may also minimize the risk for contrast-induced acute kidney injury (CI-AKI) in DM patients [5].…”
mentioning
confidence: 99%